2015
DOI: 10.1111/jipb.12345
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐trichome as a class I homeodomain‐leucine zipper gene regulates multicellular trichome development in Cucumis sativus

Abstract: Plant trichomes serve as a highly suitable model for investigating cell differentiation at the single-cell level. The regulatory genes involved in unicellular trichome development in Arabidopsis thaliana have been intensively studied, but genes regulating multicellular trichome development in plants remain unclear. Here, we characterized Cucumis sativus (cucumber) trichomes as representative multicellular and unbranched structures, and identified Micro-trichome (Mict), using map-based cloning in an F 2 segrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
102
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(104 citation statements)
references
References 41 publications
2
102
0
Order By: Relevance
“…This hypothesis was supported by data from the present study, with no observed difference in leaf trichome density but a significant difference in fruit spine density between fs1 and WT (Fig. Neighbor-joining phylogenetic tree was generated after a complete protein sequence alignment with Clustal X (1.81) Table 3 of trichomes on foliage or fruit were mapped on chromosomes 2, 3 and 6, respectively (Yang et al 2011;Li et al 2015;Pan et al 2015;Wang et al 2016;Zhao et al 2015;Cui et al 2016). In cucumber, a number of genes related to fruit spines have been identified: B for black spine, ns for numerous spines, ss for small spines, s or s1 for spine size and frequency, s2 and s3 for dense and small spines, and gl (glabrous) and tril (trichome-less) for trichomes formation (Call and Wehner 2010;Wang et al 2016).…”
Section: Inheritance and Domestication Of Fruit Spine Density Trait Isupporting
confidence: 79%
See 2 more Smart Citations
“…This hypothesis was supported by data from the present study, with no observed difference in leaf trichome density but a significant difference in fruit spine density between fs1 and WT (Fig. Neighbor-joining phylogenetic tree was generated after a complete protein sequence alignment with Clustal X (1.81) Table 3 of trichomes on foliage or fruit were mapped on chromosomes 2, 3 and 6, respectively (Yang et al 2011;Li et al 2015;Pan et al 2015;Wang et al 2016;Zhao et al 2015;Cui et al 2016). In cucumber, a number of genes related to fruit spines have been identified: B for black spine, ns for numerous spines, ss for small spines, s or s1 for spine size and frequency, s2 and s3 for dense and small spines, and gl (glabrous) and tril (trichome-less) for trichomes formation (Call and Wehner 2010;Wang et al 2016).…”
Section: Inheritance and Domestication Of Fruit Spine Density Trait Isupporting
confidence: 79%
“…Moreover, the existence of cucumber fruit spines is a precondition for the formation of fruit tubercules, as genetic analysis indicated that cucumber glabrous 1 (csgl1), a gene controlling fruit spine formation, was epistatic to the Tuberculate fruit (Tu) (Cao and Guo 1999;Cao et al 2001;Yang et al 2014;Li et al 2015). Genes gl-2, csgl1 and tril/ csgl3 controlling presence or absence of trichomes on the foliage or fruit were mapped in chromosomes 2, 3 and 6, respectively; and csgl1, tril and csgl3 were recently cloned, and both Tril and CsGL3 were found to be the same gene, Csa6M514870, in three different labs (Yang et al 2011;Li et al 2015;Pan et al 2015;Wang et al 2016;Zhao et al 2015;Cui et al 2016). Several genes related to fruit spine size and density have been identified through genetic analysis (Tkachenko 1935;Hutchins 1940;Poole 1944;Caruth 1975;Fanourakis and Simon 1987).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genetic mapping of several cucumber genes was finished. These genes included fruit dull gene ( D ) (Yang et al., ), heavy netting of mature cucumber gene ( H ) (Miao et al., ), uniform colour gene ( u ) (Yang, Yue et al., ; Yang, Zhang et al., ), fruit tumour gene ( Tu ) (Yang, Yue et al., ; Yang, Zhang et al., ; Zhang et al., ), black spine ( B ) (Li, Wen, & Weng, ), yellow fruit ( yf ) (Lu et al., ), white rind gene ( w ) (Liu et al., ), fruit bitter (Zhang et al., ), glabrous (Gl) (Cui et al., ; Zhao et al., ), fruit spine density (Zhang, Liu et al., ; Zhang, Wang et al., ). However, chromosomal mapping of palisade epidermis has not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the phenotype of the csgl cucumber mutant is controlled by a single recessive nuclear gene and that csgl1 is epistatic to the Tuberculate fruit (Tu) gene (Cao et al, 2001;Yang et al, 2014). Tu and Mict/CsGL1 were both identified, and Mict/CsGL1 was shown to be required for further differentiation of cucumber trichomes in all aerial parts of the plant, including leaves, stems, tendrils, floral organs, and fruits, but not for their initiation (Li et al, 2015;Zhao et al, 2015). Recently, a homeodomainleucine zipper gene, Tril, involved in multicellular trichome initiation in cucumber, was identified (Wang et al, 2016).…”
mentioning
confidence: 99%